PEMBENTUKAN KARATERISTIK SISWA, MELALUI PENGEMBANGAN NILAI SENI BUDAYA SUMATERA SELATAN, MEWUJUDKAN NILAI-NILAI PANCASILA KEARAH PEMBENTUKAN SIKAP NASIONALISME - Sri Wahyuningsih; Sundari Sundari; Sri Husnulwati (Jurnal Education and Development, 2023)
In the development of the technological era which is called the era of globalization, then we. How are we faced with cultural arts values ​​that have been forgotten by our generation, especially children who are still in school, both at the elementary and junior high school levels or even at the high school level, this is due to the lack of attention from related parties, especially from the parents, the school and the surrounding environment who do not provide understanding to the generation about the importance of knowledge of cultural values ​​which are directed to the historical values ​​of the nation's struggle in the formation of the characteristics of students as a generation in achieving state goals in developing an attitude of nationalism and a sense of responsibility as citizens a good country.. With an understanding of this cultural arts will certainly create a sense of nationality, by carrying out forms of positive behavior in everyday life. This research aims to shape student characteristics through cultural values, especially the culture of South Sumatra, in understanding Pancasila values ​​towards national values ​​as a form of nationalism. The research methodology is descriptive qualitative, in the form of direct observation of the object, in this case through the students of SMP PGRI 1 Palembang, as well as the community involved in this research. Qualitative research is a method for obtaining the truth and is classified as scientific research which is built on the basis of theories that develop from research and is controlled on an empirical basis.